Using the quality enhancement research initiative framework for implementation science in clinical nutrition. - Brown, Michelle; Rosenthal, Martin (Nutrition in Clinical Practice, 2025)
Implementation science (IS) offers a structured approach to bridging the gap between research and practice by facilitating the adoption of evidence‐based interventions (EBIs). One established framework within IS is the Quality Enhancement Research Initiative (QUERI), developed by the US Department of Veterans Affairs. QUERI promotes the active dissemination of EBIs through a phased roadmap: preimplementation (data to knowledge), implementation (knowledge to performance), and sustainment (performance to data). This review article explores the QUERI framework in depth and its application in clinical nutrition settings. Two case studies illustrate how QUERI can enhance implementation efforts: (1) improving inpatient malnutrition screening and (2) integrating outpatient surgical prehabilitation programs. In the first case, QUERI guides the identification of low screening and diagnosis rates, stakeholder engagement, toolkit development, and ongoing evaluation to ensure sustainability. In the second, QUERI aids in developing and adapting evidence‐based prehabilitation protocols while balancing fidelity and customization to local workflows. Both examples demonstrate the importance of structured planning, stakeholder involvement, and iterative evaluation in achieving sustained change. QUERI's emphasis on choosing a high‐volume or high‐risk problem, defining best practices, and documenting outcomes makes it a valuable tool for nutrition professionals aiming to improve outcomes through consistent application of EBIs. As clinical nutrition continues to evolve, implementation frameworks like QUERI offer a practical pathway for translating research into impactful, sustainable improvements in patient care.